2011
DOI: 10.1007/s12576-011-0167-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of monocarboxylate transporter (MCT) 1 and MCT4 in overloaded mice plantaris muscle

Abstract: A number of studies have shown that changes in muscle contractile activity regulate the expression of monocarboxylate transporters (MCTs) in the skeletal muscle. The aim of this study was to investigate the effect of functional overload on MCT1 and MCT4 protein expression. Plantaris muscles were functionally overloaded for 15 days by ablation of the synergistic muscles. MCT1 and MCT4 mRNA abundance increased by 160-161% (p < 0.01) and 265-325% (p < 0.05), respectively, after 1-3 days of functional overload. MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
(48 reference statements)
2
14
1
Order By: Relevance
“…It protects the heart from I/R injury by sustaining energy supply during ischemic stress and reducing the likelihood of cardiomyocyte cell death. Furthermore, in other studies, AMPK activation induced increases in MCT1 and MCT4 protein content in rat skeletal muscle [11,12,13]. In the current study, we also found that MCT1 and MCT4 protein expression was increased with increases in AMPK phosphorylation status during the I/R period.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It protects the heart from I/R injury by sustaining energy supply during ischemic stress and reducing the likelihood of cardiomyocyte cell death. Furthermore, in other studies, AMPK activation induced increases in MCT1 and MCT4 protein content in rat skeletal muscle [11,12,13]. In the current study, we also found that MCT1 and MCT4 protein expression was increased with increases in AMPK phosphorylation status during the I/R period.…”
Section: Discussionsupporting
confidence: 86%
“…Considering lactate may be a major energy resource for the failing heart, and may preserve or even improve myocardial performance [30,33], this possibly indicates that the hearts are failing and have a greater reliance on carbohydrates. It is suggested that regulation of MCT expression seems to be translational [13]. We did not find increased MCT expression, which may be due to the time frame of observation.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Red and white tibialis anterior (TA) muscle samples were homogenized as previously described (19,20) using lysis buffer (1% Triton X-100, 50 mm Tris-HCl, 1 mm EDTA, 1 mm EGTA, 50 mm sodium fluoride, 10 mm sodium beta-glycerol phosphate, 5 mm sodium pyrophosphate, and 2 mm dithiothreitol, pH 7.5) containing 10 mg/mL of pepstatin A, aprotinin, and leupeptin; 1 mm of Na orthovanadate, and 0.177 mg/mL of phenylmethylsulfonyl fluoride. Protein concentrations were measured by the Bradford method.…”
Section: Animalsmentioning
confidence: 99%
“…Intact, isolated single muscle fibres from mouse EDL and peroneus muscles were used [5], [26], [27]. These hindlimb skeletal muscles express NKCC1 [23], MCT1 and MCT4 [14], [24].…”
Section: Methodsmentioning
confidence: 99%